Verba Transitif Bahasa Banjar Hulu Subdialek Barabai di Desa Sungai Beringin Kecamatan Tembilahan Hilir Kabupaten Indragiri Hilir - Fitri Yani Putri, Nur; Shomary, Sudirman (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
Language is a means of communication between people in community groups as well as a means of communication between nations without language other people cannot communicate. This is in accordance with the opinion of Kridalaksana (2009: 24) "Language is a system of sound symbols used by members of a society to work together, interact, and identify themselves". The problems in this research are (1) how is the behavior syntax of transitive verbs in Banjar Hulu Language, Barabai Subdialek in Sungai Beringin Village, Tembilahan District, Indragiri Hilir Regency? (2) How semantic transitive verb behavior in Banjar Hulu Subdialek Barabai in Sungai Beringin Village, Tembilahan District, Indragiri Hilir Regency? The theory used in this study is the theory of Hasan Alwi, et al (2003) and several other supporting theories. The method used is descriptive method. The data collection technique in this research used techniques (1) observation, (2) proficient, (3) recording, and (4) taking notes. The results of this study concluded that (1) the syntactic behavior of transitive verbs contained in the Banjar Hulu language, Barabai sub-dialect in Sungai Beringin Village, Tembilahan District, Indragiri Hilir Regency, there are three: (a) transitive verbs consisting of: 17 data, (b) dwitransitive verbs which consists of: 16 data, (c) semitransitive verbs consisting of: 5 data. (2) there are four semantic transitive verb behavior in the Banjar Hulu language, Barabai sub-dialect in Sungai Beringin Village, Tembilahan District, Indragiri Hilir Regency, there are four: (a) verbs containing the meaning of action consist of: 7 data, (b) verbs containing process meanings consisting of: 3 data, (c) the verb contains the meaning of the command consisting of: 1 data, (d) the verb contains the meaning of the state which consists of: 4 data.